Study of Blended-Learning Method Assisted By Edmodo in Teaching English at State Vocational School in Deli Serdang - Rini Ekayati (BIRCU, 2019)
This study aims to describe blended-learning method assisted by Edmodo in teaching English at State Vocational School in Deli Serdang. Descriptive qualitative method was used in this study in order to examine factors, expected methods, and the pattern in teaching English at State Vocational School in Deli Serdang, by administrating questioner, interview, and observation as source of data taken from the sample. The research was conducted at two State Vocational Schools in Deli Serdang, namely SMK Negeri 1 Percut and SMK Negeri. The results show that there are: 1) 7 factors to be considered in selecting the teaching method for English subject, such as learning objectives, materials, resources, members of the learning process, facilities, time, and the number of study groups), 2) the expected method of teaching English in the vocational school are the student center learning method and technology-based learning method, and 3) there are 2 patterns of blended-learning learning methods assisted by Edmodo, and which are obtained based on lesson time.